Comparative transcriptomic analysis provides key genetic resources in clove basil (Ocimum gratissimum) under cadmium stress - Wang, Bin; Wang, Yukun; Yuan, Xiao; Jiang, Yuanyuan; Zhu, Yunna; Kang, Xinmiao; He, Jinming; Xiao, Yanhui (Frontiers in Genetics, 2023)
Planting aromatic plant might be a promising strategy for safely utilizing heavy metal (HM)-contaminated soils, as HMs in essential oil could be completely excluded using some special technologies with ease. Clove basil (Ocimum gratissimum L.) is an important aromatic plant used in essential oil production. Improving cadmium (Cd) tolerance in clove basil can increase its production and improve the utilization efficiency of Cd-contaminated soils. However, the lack of genomic information on clove basil greatly restricts molecular studies and applications in phytoremediation. In this study, we demonstrated that high levels of Cd treatments (0.8, 1.6 and 6.5 mg/L) significantly impacted the growth and physiological attributes of clove basil. Cd contents in clove basil tissues increased with treatment concentrations. To identify Cd stress-responsive genes, we conducted a comparative transcriptomic analysis using seedlings cultured in the Hoagland’s solution without Cd ion (control) or containing 1.6 mg/L CdCl2 (a moderate concentration of Cd stress for clove basil seedlings). A total of 104.38 Gb clean data with high-quality were generated in clove basil under Cd stress through Illumina sequencing. More than 1,800 differentially expressed genes (DEGs) were identified after Cd treatment. The reliability and reproducibility of the transcriptomic data were validated through qRT-PCR analysis and Sanger sequencing. KEGG classification analysis identified the “MAPK signaling pathway”, “plant hormone signal transduction” and “plant-pathogen interaction” as the top three pathways. DEGs were divided into five clusters based on their expression patterns during Cd stress. The functional annotation of DEGs indicated that down-regulated DEGs were mainly involved in the “photosynthesis system”, whereas up-regulated DEGs were significantly assigned to the “MAPK signaling pathway” and “plant-pathogen interaction pathway”. Furthermore, we identified a total of 78 transcription factors (TFs), including members of bHLH, WRKY, AP2/ERF and MYB family. The expression of six bHLH genes, one WRKY and one ERF genes were significantly induced by Cd stress, suggesting that these TFs might play essential roles in regulating Cd stress responses. Overall, our study provides key genetic resources and new insights into Cd adaption mechanisms in clove basil.